Effectiveness of Subcutaneous Bupivacaine–Ketamine Wound Infiltration in Reducing Post-Cesarean Section Pain: A Randomized, Double-Blind, Controlled Trial - Nadra Septiadi Nadra; Riyadh Firdaus Riyadh; Besthadi Sukmono Besthadi; Rafidya Indah Septica Rafidya Indah (Frontiers on Healthcare Research, 2026)
Background: Effective postoperative analgesia supports maternal recovery after cesarean delivery, yet subcutaneous local anesthetic infiltration, a simple technique well suited to resource-limited settings, typically provides only 3–6 hours of relief. Ketamine, an NMDA-receptor antagonist with analgesic activity at subanesthetic doses, may extend this window, but evidence in cesarean delivery remains limited.Objective: To determine whether adding subcutaneous ketamine to bupivacaine infiltration reduces rescue opioid requirement after cesarean delivery. Methods: In this randomized, double-blind, controlled trial at Tangerang Regional General Hospital, Indonesia, 60 women undergoing cesarean delivery under spinal anesthesia were allocated 1:1 to subcutaneous infiltration of 0.25% bupivacaine with ketamine 0.9 mg/kg (Group A, n = 30) or 0.25% bupivacaine alone (Group B, n = 30) before wound closure. The primary outcome was total rescue fentanyl requirement in the first 24 postoperative hours. Results: The median 24-hour fentanyl requirement was lower with ketamine (30 [0–90] vs 90 [0–150] mcg; p < 0.001), and fewer participants required rescue fentanyl at all (56.7% vs 76.7%), with a lower cumulative group dose (840 vs 2240 mcg). Group A also had lower pain scores from hour 7 onward, a longer interval to the first rescue request (810 vs 420 min; p = 0.019), and earlier first mobilization (585 vs 810 min; p < 0.001). No serious adverse events occurred in either group. Conclusion: Adding subcutaneous ketamine to bupivacaine infiltration lowered the rescue opioid requirement and supported faster recovery after cesarean delivery, offering a practical, low-cost addition to multimodal analgesia in resource-limited settings.